The Effects of Accentuated Eccentric Loading on Barbell and Trap Bar Countermovement Jumps - Christopher Taber; Calin Butler; Victoria Dabek; Benjamin Kochan; Kyle McCormick; Emily Petro; Timothy Suchomel; Justin Merrigan (International Journal of Strength and Conditioning, 2023)
This study examined effects of accentuated eccentric loading (AEL) on barbell and trap bar loaded countermovement jumps (LCMJ). Twenty-one subjects (16 male, 5 female; Age: 23.5 ± 1.8 years; Body mass: 81.4 ± 10.6 kg; Height: 176.9 ± 7.2 cm; Training age: 7.1 ± 2.6 years) participated in this study. Upon establishing one repetition maximum and baseline jumping conditions, three experimental loading sessions were completed in random order. Barbell and trap bar LCMJ were performed with a spectrum of fixed loads from 20-50 kg during control conditions and with additional AEL loads of 10, 20, or 30 kg for experimental conditions. According to coefficients of variation (<10%), jump height, modified reactive strength index (mRSI), force, impulse, and duration measures were considered reliable across conditions. Mixed effect models analyzed effects of AEL against fixed loading in trap bar and barbell LCMJ (p < 0.05). Compared to the control condition, AEL produced negligible reductions in jump height during barbell LCMJ and small reductions during trap bar LCMJ. Modified reactive strength indexes were reduced by AEL during barbell LCMJ but not trap bar LCMJ. Average braking forces were greater in AEL conditions, while propulsive impulse was lower in the AEL conditions. The barbell LCMJ with AEL resulted in longer propulsive durations and unchanged braking durations, while propulsive and braking durations were lower during trap bar LCMJ with AEL compared to control conditions. This investigation revealed that use of AEL increases eccentric braking forces but decreases propulsive phase outputs, which subsequently may result in negligible to small acute decreases in LCMJ height. Implementing AEL during LCMJ may be an effective strategy to improve deceleration / eccentric abilities. Future research should explore longitudinal power and deceleration adaptations, while concomitantly improving acutely altered movement mechanics from AEL.